(untitled) (Medico Legal Update, 2019)
Background/Objectives: The aim of this study was to investigate the relationship between social support according to gender, grade, and residential type and between social support and life satisfaction of college student. Method/Statistical Analysis: A survey was conducted among 444 college students in Gangwon area, South Korea. Questionnaire was composed of 32 items which consist of 27 items of social support and 5 items of life satisfaction. Findings: Analysis showed that male in the relationship between social supports according to gender showed a significant difference in the teaching support. The relationship between social supports according to grade showed significant differences in parents, teaching support. The boarding house receives more friend support than other residential type. Social support and life satisfaction showed a correlation, teaching support and life satisfaction was the highest coefficient of correlation. Improvements/Applications: There was a significant difference in teaching support among males than female’s students, and there was a significant difference in teaching support among the lower grades than in the upper grades